Ragam Budaya dan Kekayaan Ekologi sebagai Potensi Pengembangan Wellness Tourism di Kalimantan Timur; Studi Kelembagaan Masyarakat Kutai Adat Lawas Sumping Layang Kedang Ipil Kutai Kartanegara. - I Wayan Lanang Nala; I Wayan Sudarmayasa; Hira, Tauhid; Arif Aidil Adha; Puji Kharisma Arifin (EDUTOURISM Journal Of Tourism Research, 2024)
Post-pandemic COVID-19 has highlighted wellness tourism as a promising niche in Indonesia, driven by increased health awareness and supported by initiatives like the CHSE (Cleanliness, Health, Safety, and Environmental Sustainability) Protocols. East Kalimantan, with its unique cultural and natural heritage, offers significant potential for wellness tourism development. This study evaluates the cultural richness, ecological assets, and opportunities for wellness experiences in East Kalimantan, emphasizing the role of community engagement in economic empowerment, cultural preservation, and environmental management.Using a qualitative approach with descriptive analysis, the research includes key informant interviews with cultural leaders of Kutai Adat Lawas Sumping Layang in Kedang Ipil, supplemented by direct observation and secondary data. Thematic analysis and data triangulation ensure validity and provide insights into the role of customary institutions in wellness tourism. The findings identify traditional practices, such as Belian Namang and Nutuk Beham, as unique wellness experiences. The ecological assets, including village and customary forests integral to local livelihoods, present holistic wellness opportunities. Customary community structures are crucial in preserving traditions and supporting wellness tourism as a sustainable product. The integration of cultural and ecological elements positions Kedang Ipil, Kutai Kartanegara, as a strategic site for wellness tourism, fostering sustainable development through cultural heritage and environmental